1999
DOI: 10.1136/gut.44.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin versus pneumatic dilatation in the treatment of achalasia: a randomised trial

Abstract: Background-Intrasphincteric injection of botulinum toxin is a new treatment option for achalasia. Aims-To compare the immediate and long term eYcacy of botulinum toxin with that of pneumatic dilatation. Methods-Symptomatic patients with achalasia were randomised to botulinum toxin (22 patients, median age 57 years) or pneumatic dilatation (20 patients, median age 56 years). Symptom scores were assessed initially, and at one, three, six, nine, and 12 months after treatment. Objective assessment included oesopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
132
2
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(145 citation statements)
references
References 13 publications
(18 reference statements)
5
132
2
6
Order By: Relevance
“…A randomized controlled trial published in 2017 comparing POEM with pneumatic dilation found the POEM procedure to be more efficacious in terms of therapeutic success, but also more likely to result in post-procedure reflux oesophagitis 61 . The preceding discussion makes no mention of medical treatments for achalasia, specifically botulinum toxin [62][63][64][65] , calcium-channel blockers 66 , nitrates 66 and phosphodiesterase type 5 inhibitors 67 primarily because, although these agents provide some symptomatic benefit, they are not durable therapies and they do not halt the disease progression toward oesophageal decompensation characterized by dilatation and food retention. For example, in the case of botulinum toxin injected into the LES, about two-thirds of patients with achalasia report an improvement in dysphagia, but most relapse within a year and repeat treatments have diminished effectiveness, making it a poor firstline therapy [62][63][64][65] .…”
Section: Poemmentioning
confidence: 99%
“…A randomized controlled trial published in 2017 comparing POEM with pneumatic dilation found the POEM procedure to be more efficacious in terms of therapeutic success, but also more likely to result in post-procedure reflux oesophagitis 61 . The preceding discussion makes no mention of medical treatments for achalasia, specifically botulinum toxin [62][63][64][65] , calcium-channel blockers 66 , nitrates 66 and phosphodiesterase type 5 inhibitors 67 primarily because, although these agents provide some symptomatic benefit, they are not durable therapies and they do not halt the disease progression toward oesophageal decompensation characterized by dilatation and food retention. For example, in the case of botulinum toxin injected into the LES, about two-thirds of patients with achalasia report an improvement in dysphagia, but most relapse within a year and repeat treatments have diminished effectiveness, making it a poor firstline therapy [62][63][64][65] .…”
Section: Poemmentioning
confidence: 99%
“…achieve a stable effect on symptoms, and in the experience of other authors, the long-term results appear to be less satisfactory than those obtained by pneumatic dilatation. 7 Although the exact role of botulinum toxin is still to be de®ned, there is widespread agreement that this approach is useful for patients who cannot undergo dilatation and who are not surgical candidates. 8 The use of botulinum toxin has been found to be remarkably safe; however, the possibility that it could induce oesophagogastric re¯ux has not yet been formally evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing the initial symptomatic relief after Botox injection with the one after PD or LHM, 5 randomized studies have shown a similar effect, but a fastter loss of response in patients treated with Botox (30)(31)(32)(33).…”
Section: Endoscopic Injection Of Botoxmentioning
confidence: 99%